Development of street lighting systems based on projects in the field of energy conservation and the use of alternative energy sources - M. V. Chernovalova; I. M. Makarova (Путеводитель предпринимателя, 2022)
The article presents the results of the analysis of the current electricity consumption in different countries. Various directions and approaches to reducing the carbon footprint have been analyzed, which have shown the high importance of implementing projects in the field of energy conservation and alternative energy. It has been established that the implementation of these projects will allow not only to reduce the harm caused to the environment, but also to obtain a significant economic effect due to energy conservation and the use of distributed energy technologies. An example of the implementation of projects for the modernization of street lighting systems in the Smolensk region, based on the use of energy–saving technologies and solar panels, is considered. The results of the analysis showed that the main difficulty in the implementation of projects in the field of development of street lighting systems on the basis of this approach is associated with the lack of sufficient financial resources, which is due to their high science intensity. Various mechanisms and practices of attracting investments in these projects in the USA, Germany and Russia were considered.